TINGKAT KEMAMPUAN SISWA DALAM MENGENAL KARAKTERISTIK BERITA HOAX DI MEDIA SOSIAL PADA SISWA SMA NEGERI 1 ABIANSEMAL - Kotaniartha, I Wayan; Ayu Windu Sari (Jurnal Kajian Ilmu Komunikasi, 2021)
The low-level literacy education in Indonesia causes hoax news trusted easily, where currently social media users are not only teenagers but also children, and parents. A study entitled "The Level of Student Ability in Recognizing Characteristics of Hoax News on Social Media (Case Study on SMA N 1 Abainsemal)" aimed at determining the level of students' ability to recognize the characteristics of hoax news on social media. This study was a quantitative approach with 78 research subjects. To simplify research, the data were collected by using questionnaire instruments that have been chosen for the answer. Then the data were analyzed using quantitative descriptive analysis techniques. Based on the results of the analysis, it showed that the students’ ability to recognize the characteristics of hoax news on social media was excellent/ very capable. The result of questionnaire proved that 77 or 98.7% out of 78 respondents were categorized very capable in recognizing the impact of hoax news on social media which causes hate and anxiety. The lowest achievement 78 respondents, there were 47 or 60.3% respondents were categorized fair capable in recognizing the characteristics of unequal hoax news